Effects of a High-Fat Diet on Intestinal and Gonadal Metabolism in Female and Male Sea Cucumber Apostichopus japonicus - Zhang, Shuangyan; Ru, Xiaoshang; Zhang, Libin; Gonçalves, David; Yang, Hongsheng; Xu, Jialei (Biology, 2023)
Parental nutrient reserves are directly related to reproductive performance in sea cucumbers. This study focused on the lipid requirements of male and female sea cucumbers Apostichopus japonicus during the reproductive stage and analyzed their physiological responses to a high-fat diet (HFD). The intestinal lipid metabolites and microbiome profile changed significantly in animals fed with the HFD, as given by an upregulation of metabolites related to lipid metabolism and an increase in the predominance of Proteobacteria in the microbiome, respectively. The metabolic responses of male and female sea cucumbers to the HFD differed, which in turn could have triggered sex-related differences in the intestinal microbiome. These results suggest that the lipid content in diets can be differentially adjusted for male and female sea cucumbers to improve nutrition and promote reproduction. This data contributes to a better understanding of the reproductive biology and sex differences of sea cucumbers.
Number: 2
Keywords: high-fat diet; intestinal microbes; physiological metabolic responses; sea cucumber; sex differences